Research on the performance of industrial innovation of small and medium-sized enterprises in China - Guoqing Lu; Peng Dai; Xia Zhang (China Political Economy (CPE), 2018)
Purpose The purpose of this paper is to test the relationship between innovation performance and innovation spillover effects, innovation inputs, innovation outputs and industrial effects. Design/methodology/approach The analysis framework including variables such as innovation spillover effect, innovation input, innovation output and industrial effect was constructed. Through the investigation and analysis of the innovation activities of China's GEM listed companies in 2014-2016, the innovation performance and the above factors were tested. Findings The research shows that enterprise performance has a significant positive correlation with innovation input and innovation output, but there is no significant correlation or even negative correlation with innovation environment and industry background such as government support and innovation opportunities, and the spillover effect is significant. The negative correlation is also negatively correlated with innovative human capital investment, company age and company Q. Originality/value Innovation is the real source of economic growth, and industrial innovation is the system integration of technological innovation, product innovation, market innovation, etc., which is the basic determinant of national competitiveness.
Keywords: 330; GEM listed company; Industrial innovation; Innovation performance; Innovation spillover effect